PENDAMPINGAN UMKM TELUR ASIN DALAM MENINGKATKAN KUALITAS DAN PEMASARAN PRODUK DI KELURAHAN CIKUYA - Nassir Agustiawan, M; Delia Ayunda Maulia; Widia Lestari; Nur Ferah; Nasihin Setiawan Anwar; Lola Amanda; Berliana Sefriani Damanik; Lukman Hakim; Riza Eka Fatmawati; Lina Maulida; Silvi Alfiana (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The 44th Student Internship Program (KKM) in Cikuya Village was implemented with a focus on mentoring salted egg MSMEs in improving product quality and marketing. This activity was motivated by the large potential of the salted egg business in the region that has not been optimally optimized, both in terms of product quality and marketing strategies. The mentoring was carried out through several stages, including training on improving production quality, introducing flavor and packaging innovations, and digital marketing strategies to expand market reach. The method used was a participatory approach by directly involving MSME actors in training sessions, discussions, and field practice. The results of the activity showed an increase in MSME understanding and skills in maintaining product quality, using more attractive packaging, and utilizing social media as a promotional tool. With this mentoring, it is hoped that salted egg MSMEs in Cikuya Village will be able to increase their competitiveness and contribute more to the local economy.